1993
DOI: 10.1007/bf02860501
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of neonatal septicemia with multidrug resistantKlebsiella Pneumoniae

Abstract: A nosocomial outbreak of neonatal septicemia due to K. pneumoniae occurred in nursery during June-July, 1991. Klebsiella pneumoniae (Klebocin type 314) was recovered from blood of 33 (70.2%) of 47 neonates with septicemia. Multiple drug resistance was observed in all the cases. The same strain of K. pneumoniae was recovered from the neonates and environment of nursery and labour room as well. The outbreak was attributable to environmental dissemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…It can also be present as colonizers on the hands of the health care workers. There are also frequent reports of neonatal septicemia outbreaks due to Klebsiella pneumoniae in nursery and NICUs [20]. In the present study, the authors observed an outbreak of ESBL producing Klebsiella pneumoniae during May-June 2006.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It can also be present as colonizers on the hands of the health care workers. There are also frequent reports of neonatal septicemia outbreaks due to Klebsiella pneumoniae in nursery and NICUs [20]. In the present study, the authors observed an outbreak of ESBL producing Klebsiella pneumoniae during May-June 2006.…”
Section: Discussionmentioning
confidence: 85%
“…Klebsiella pneumoniae was more significantly implicated in sepsis occurring among in-born babies, while Acinetobacter species and CONS were significantly associated with out-born babies. Klebsiella pneumoniae is commonly found in the environment of the neonatal intensive care units and nursery [20]. It can also be present as colonizers on the hands of the health care workers.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations in neonatal infections due to Klebsiella in the nursery have been reported in 1993. [8] Neonatal septicaemia due to ESBL producing K. pneumoniae was reported to produce 25% mortality. [9] Eighty percent mortality was reported during an ESBL outbreak in NICU of JIPMER, Pondicherry.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26] Infections caused by antibiotic-resistant bacteria are a particularly grave global problem27-29 not only because of the increased morbidity and mortality associated with these infections but also because they lead to increased use of expensive antimicrobial agents.…”
Section: Background and Rationalementioning
confidence: 99%